PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWANPERUSAHAAN PT LUAH UWANG INDONESIA DI SAMARINDA - Lasnoto Lasnoto (Jurnal Ekonomi dan Manajemen, 2017)
Analysis of the Effect of Work Discipline on Work Productivity Employees Company PT Luah Uwang Indonesia in Samarinda. The purpose of this study is to know and analyze how much influence of Work Discipline Against Work Productivity Employees Company PT Luah Uwang Indonesia in Samarinda. The result of simple linear regression analysis shows that the regression equation is described and the equation formulation is Y = 0.750 + 0.750 X This means that if X = 0, the level or magnitude of productivity variable (Y) will be 75% means there is an average increase in productivity (Y) of 0.750 for each one unit change in the work discipline variables (X) and constants are considered fixed. The results showed that the value of F arithmetic amounted to 18,597 when viewed from the significant value then obtained the value of sig 0.00 <a = 0.05 then Ho is rejected and Ha accepted. This means there is a relationship between variable discipline / independent (X) on productivity variables/dependent (Y). The results showed that there is a positive influence between discipline on employee productivity indicated by t arithmetic = 4.312 and t table = 0.433 then t arithmetic > t table Medium R Square value of 0.470 Means that the independent variable work discipline (X) is able to explain the dependent variable work productivity (Y) of 47% while the remaining 53% is influenced by other variables outside the study.